Icons, Images, Interpretations: Arrian,Lukian, their Relationship, and Alexander at the Kydnos - Sabine Müller (Karanos, 2018)
Alexander was the most prominent Argead and one of the major figures in Second Sophistic literature. The Second Sophistic authors had their own respective images of Alexander, treatment of their sources, and intention to write about him. This paper aims at exploring Lucian's ironic response to the historiographical Alexander images in his time. It will be argued that by ridiculing the current Alexander images in Second Sophistic literature, particularly as provided by Arrian's Anabasis, Lucian did not mean to make fun of the historical Alexander but of his reception and the bias and artifice involved.